PREDICATIVE MODAL TYPE OF VERBAL INFINITIVE USAGE IN QUANTITATIVE MEASUREMENT - Shigurov, Victor; Shigurova , Tatyana (Revista Inclusiones, 2020)
This paper aims to study the degrees of correspondence of the differential features of substantive representatives of the verb token that explicate the peripheral zone of the infinitives on the modalation scale, on the one hand, to the differential attributes of the core representatives of the infinitives and, on the other, to the core representatives of the introductory modal words and expressions of verbal origin. Using the method of oppositional analysis and indexation, the authors determine the main stages of the transposition of the infinitive (vidat ’to see’) into the semantic and syntactic category of introductory modal units representing the position of the modus subject in the phrase and explore the proportion of verb attributes and introductory modal words and expressions in the structure of the peripheral infinitive vidat ’to see’. The study has established that when using the impersonal main part as a predicate in a complex sentence that has an explanatory clause in it, the infinitive vidat ’to see’ begins to move along the transition scale in the direction of introductory modal units, showing 81% correspondence (similarities and differences) to the core infinitive (vidat ’to see’) and 18% correspondence to the core introductory modal word (vidat ‘apparently’). The weakening of verb properties in the infinitive is due to semantic and syntactic reasons, in particular, a reduction in its functional potential in an impersonal construction. The research results can be used in developing the theory of parts of speech and word classes integrating different parts of speech, as well as in creating transpositional grammar of the Russian language.